Law and economics of possession / edited by Yun-chien Chang. - Chang, Yun-chien (Cambridge University Press, 2015)
Possession is a key concept in both the common and civil law, but it has hitherto received little scrutiny. Law and Economics of Possession uses insights from economics, psychology and history to analyse possession in law, compare and contrast possession with ownership, break down the elements of possession as a fact and as a right, challenge the adage that 'possession is 9/10 of the law', examine possession as notice, explain the heuristics of possession, debunk the behavioural studies which confuse possession with ownership, explore the LightSquared dispute from the perspective of 'possession' of spectrum frequency and provide new insights to old questions such as first possession, adverse possession and property jurisdiction. The authors include leading property scholars, who examine possession laws in, among others, the USA, UK, China, Taiwan, Japan, Germany, France, Israel, the Netherlands, Spain, Portugal, Italy, Austria.